Cr isotopic insights into ca. 1.9 Ga oxidative weathering of the continents using the Beaverlodge Lake paleosol, Northwest Territories, Canada. Issue 5 (21st April 2019) - Toma, Jonathan; Holmden, Chris; Shakotko, Paul; Pan, Yuanming; Ootes, Luke
Abstract: The ca . 1.9 Ga Beaverlodge Lake paleosol was studied using redox‐sensitive Cr isotopes in order to determine the isotopic response to paleoweathering of a rhyodacite parent rock 500 million years after the Great Oxidation Event. Redox reactions occurring in modern weathering environments produce Cr(VI) that is enriched in heavy Cr isotopes compared to the igneous inventory. Cr(VI) species are soluble and easily leached from soils into streams and rivers, thus, leaving particle‐reactive and isotopically light Cr(III) species to build up in soils. The Beaverlodge Lake paleosol and two other published weathering profiles of similar age, the Flin Flon and Schreiber Beach paleosols, are not as isotopically light as modern soils, indicating that rivers were not as isotopically heavy at that time. Considering that the global average δ 53 Cr value for the oxidative weathering flux of Cr to the oceans today is just 0.27 ± 0.30‰ (1σ) based on a steady‐state analysis of the modern ocean Cr cycle, the oxidative weathering flux of Cr to the oceans at ca . 1.9 Ga would have likely been shifted to lower δ 53 Cr values, and possibly lower than the igneous inventory (–0.12 ± 0.10‰, 2σ). Mn oxides are the main oxidant of Cr(III) in modern soils, but there is no evidence that they formed in the studied paleosols. Cr(VI) may have formed by direct oxidation of Cr(III) using molecular oxygen or H2 O2, but neither pathway is as efficient as Mn oxides for producing Cr(VI). The picture that emerges from this and other studies of Cr isotope variation in ca . 1.9 Ga paleosols is of atmospheric oxygen concentrations that are high enough to oxidize iron, but too low to oxidize Mn, resulting in low Cr(VI) inventories in Earth surface environments.